Kraftübertragung und Fahrbahnverschleiß durch Spikereifen - Gültlinger, Johannes (Karlsruher Schriftenreihe Fahrzeugsystemtechnik / Institut für Fahrzeugsystemtechnik, 2015)
While studded tires improve force transmission on icy roads, they cause damage of the road surface when running on bare roads. This report describes the interaction between studded tire and road and identifies mechanisms involved in the force transmission and road wear caused by studded tires. Test methods for experimental investigations are presented as well as the influence of different parameters on force transmission and road wear.